Can we predict glioblastoma, IDH wild type with FGFR3::TACC3 fusion morphologically? - Soylemez\\-Akkurt, T.; Kusku\\-Cabuk, F.; Ersen\\-Danyeli, A. (WILEY, 2023)
20th International Congress of Neuropathology, Berlin, GERMANY, SEP 13-16, 2023